Impact of platelet-lymphocyte ratio after robot-assisted partial nephrectomy with renorrhaphy - Tomoki Taniguchi; Kentaro Muraoka; Kohei Nishikawa; Yoshinori Ikehata; Kiyoshi Setoguchi; Suguru Oka; Shin Ebara; Akira Fujisaki; Kazuhide Makiyama; Takahiro Inoue; Hiroshi Kitamura; Kazutaka Saito; et al. (Scientific Reports)
Abstract Renorrhaphy is often performed after tumor resection during robotic-assisted laparoscopic partial nephrectomy (RAPN). This study aimed to investigate the association between renorrhaphy performance and inflammatory markers. A retrospective cohort study was conducted including patients with renal cell carcinoma who underwent RAPN at eight institutions in Japan between April 2016 and November 2023. The primary endpoint was the association between the renorrhaphy performance in RAPN and the postoperative inflammatory markers. The secondary endpoints were perioperative outcomes in patients with and without renorrhaphy. The patients were divided into two groups at the time of RAPN: those who underwent renorrhaphy (renorrhaphy group) and those who did not (omitted group). In total, 934 patients were enrolled in this study. After propensity score matching, the rate of change in C-reactive protein and neutrophil-lymphocyte ratio on postoperative day 28 were not significant difference between the two groups. In contrast, the rate of change in platelet-lymphocyte ratio (PLR) on postoperative day 28 was significantly higher in renorrhaphy group than omitted group. Regarding surgical outcomes, the renorrhaphy group had a significantly longer hospital stay, operative time, and warm ischemia time (P = 0.038, P = 0.022, and P = 0.009, respectively) than the omitted group did. Furthermore, the omitted group had a significantly higher rate of Trifecta achievement than the renorrhaphy group did. This study demonstrated that renorrhaphy performance in RAPN was significantly associated with the higher value of postoperative PLR.